Promoting Family Wellness and Preventing Child Maltreatment Fundamentals for Thinking and Action - Nelson, Geoffrey; Peirson, Leslea; Prilleltensky, Isaac (University of Toronto Press, 2020)
Based on extensive research over many years, with a broad range of participants in Canada and internationally, this collection of essays is an important contribution to the child welfare agenda. It deals with the promotion of emotional well-being in families, and the prevention of child maltreatment. Values, policies and resources are examined as both facilitators of, and barriers to, effective action.The authors interviewed nearly 150 people, including researchers, policy makers, social workers and clients of the child welfare system. Both theoretical and practical issues emerge, as the authors discuss the social context of abuse and the scientific context wherein policy is made. They conclude that the following social conditions are essential in effectively reducing abuse: upheld values of self-determination and the health of children; sufficient material and psychological resources for children and families; family-friendly parental leave and child support policies, and empirically grounded and tested prevention programs. Contained within the work is extensive examination of current issues in Aboriginal child welfare. The authors advocate certain collective approaches to child-raising, inspired by current and historical Aboriginal practices. Promoting Family Wellness is of relevance to all those involved in child welfare, and to researchers and students too. It is readable and clear enough to be of interest to the general reader who is interested in this intellectually complex and emotionally fraught topic